STUDENTS’ PREDICTED VS. ACTUAL TOEFL SCORES: FINDINGS FROM A SELF-ASSESSMENT SURVEY - Arni Sukmiarni (Jurnal Sastra - Studi Ilmiah Sastra, 2025)
This study aims to explore students’ self-assessment of their English proficiency on the TOEFL test by predicting their anticipated scores with the actual results they achieved. The students performed a self-assessment consisting of a set of questionnaires about how they thought they would do on the TOEFL test, about their skills of listening, reading, grammar, and sentence structure, and their confidence when doing TOEFL practices and strategies. The results show that most students’ predictions of their TOEFL scores were rather close. The responses to students’ predictions indicate that some students think that they are less capable than they really are, while others seem to have a slight tendency to overestimate. Overall, the results indicate that the students need more personalized TOEFL learning strategies, with an emphasis on regular practice.